Engaging with Cities of the Future : a Perspective (Asian Development Bank, 2017)
"Inefficient and uncompetitive cities inhibit economic growth and inclusive development. Integrated urban planning will help stem the decline of Asian and Pacific cities, spelling the difference between a future of gloom or glory in the region. The technical assistance Establishing the Future Cities Program in the Asia and Pacific Region identifies new approaches, particularly the Future Cities approach, to address the challenges of urbanization. The program reviewed the entire ecosystem of how to develop livable cities and served as a testing ground for new or improved solutions. This publication captures insights from work in six pilot cases in Tbilisi, Mandalay, Greater Suva Area, Ulaanbaatar, Makassar, and Bandung."--